Introduction to the January 2025 Issue - Peter H. Siegel (IEEE Journal of Microwaves)
As we begin our fifth year of publication, we are moving into phase two of our mission to create a stand-alone, high-quality, open access journal that does not directly compete with our core publications within the Microwave Theory and Technology Society (MTT-S). Towards that end, we are making major changes to our internal Editorial Board structure and paper screening methods. We will continue to focus on broad-appeal articles and cross-disciplinary topics that cover the entire range of microwave techniques and applications, and especially those subjects that breach traditional boundaries between engineering and science. We will also continue to bring you special editorial features on a regular basis, including this month's Microwave Pioneer article on UCLA's Mau-Chung Frank Chang. As our paper queue has expanded, we have decided to move to bimonthly, rather than quarterly issue releases. We hope this will reduce our paper queue and decrease the time between article submission and final issue-paginated release. Our January issue content includes 19 regular papers spanning topics that include wearable smart skins, batteryless IoT devices, astronaut hand gesture recognition, THz chiral structures, and metamaterial transmitarrays. We also bring you more than our usual quantity of the more core microwave filter, transmission line, antennas, and waveguide component papers, and a couple of papers on radar instruments and techniques.